2010
DOI: 10.1152/ajpregu.00055.2009
|View full text |Cite
|
Sign up to set email alerts
|

Exercise changes regional vascular control by commissural NTS in spontaneously hypertensive rats

Abstract: Ogihara CA, Schoorlemmer GHM, Levada AC, Pithon-Curi TC, Curi R, Lopes OU, Colombari E, Sato MA. Exercise changes regional vascular control by commissural NTS in spontaneously hypertensive rats. Am J Physiol Regul Integr Comp Physiol 299: R291-R297, 2010. First published April 21, 2010 doi:10.1152/ajpregu.00055.2009.-Inhibition of the commissural nucleus of the solitary tract (commNTS) induces a fall in sympathetic nerve activity and blood pressure in spontaneously hypertensive rats (SHR), which suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…The commNTS also receives inputs from arterial chemoreceptors and seems to be highly sensitive to carotid chemore-www.bjournal.com.br Braz J Med Biol Res 44 (9) 2011 ceptor stimulation. A recent study observed that swimming exercise induced changes in commNTS neurons that were demonstrated by a greater enhancement of hindlimb vasodilatation in WKY vs SHR rats in response to the GABAergic inhibition of these neurons (55). This study reinforces the view that the CNS participates in the cardiovascular adaptations to exercise training and proposes a differential vascular regulation mediated by the CNS.…”
Section: Modulation By Brainstem Areassupporting
confidence: 81%
“…The commNTS also receives inputs from arterial chemoreceptors and seems to be highly sensitive to carotid chemore-www.bjournal.com.br Braz J Med Biol Res 44 (9) 2011 ceptor stimulation. A recent study observed that swimming exercise induced changes in commNTS neurons that were demonstrated by a greater enhancement of hindlimb vasodilatation in WKY vs SHR rats in response to the GABAergic inhibition of these neurons (55). This study reinforces the view that the CNS participates in the cardiovascular adaptations to exercise training and proposes a differential vascular regulation mediated by the CNS.…”
Section: Modulation By Brainstem Areassupporting
confidence: 81%
“…Importantly, EXT normalizes the carotid body chemoreflex by preventing an increase in afferent carotid body chemoreceptor activity in rabbit with chronic heart failure . A recent study also shows that swimming exercise enhances the GABAergic inhibition in the commNTS neurons of SHR . The above evidence indicates that ExT leads to a reduction in afferent activity as well as neuronal activity in the commNTS.…”
Section: Discussionmentioning
confidence: 82%
“…S oleus muscles from both legs of each animal were collected and stored at –80 °C for determination of CS activity (n=8 per group), a measure of muscle oxidative capacity, to determine the efficacy of the training protocol [47]. CS activity was measured from whole muscle homogenate by using commerically available citrate synthase activity assay kit (Sigma Aldrich).…”
Section: Methodsmentioning
confidence: 99%